NADESPENÇA - Oliveira, Sebastião; Oliveira, Alexandre; Leonel, Douglas; Silva, Thiago; Everson, Elias; Gabriel, Douglas; Neuwirth, Luiz Filipe (CIPEEX, 2022)
IN ORDER TO COLLABORATE WITH A MORE ECOLOGICALLY CORRECT SOCIETY, IT WAS THOUGHT OF DEVELOPING A PROJECT THAT AIMS TO PREVENT FOOD WASTE, THUS COLLABORATING JOINTLY IN SUSTAINABILITY WITH THE ECONOMIC ENVIRONMENT. THIS WORK PRESENTS THE CREATION OF AN APPLICATION THAT COLLABORATES IN A POSITIVE WAY WITH THE USER, REGISTERING HIS PURCHASES, GIVING PROTAGONISM TO THE FOOD, AND HELPING ITS USERS WITH THE PREVENTION OF FOOD WASTE AND INFORMING THEM OF ITS VALIDITY AND COLLABORATING WITH MORE EFFECTIVE METHODS OF CONSCIOUS CONSUMPTION. FOR ITS DEVELOPMENT AND APPLICATION IT WILL BE NECESSARY A GROUP OF DEVELOPERS TOGETHER WITH AN EFFECTIVE FRAMEWORK FOR THE PROJECT; A SCRUM TEAM AIMING AT A FAST PRODUCT DELIVERY; A RESEARCH GROUP FOCUSED ON THE HIGH QUALITY OF THE PROJECT; A DATABASE FOR INFORMATION COLLECTION AND COMPARISONS. THROUGH THE PROJECT, DATA WILL BE COLLECTED FROM THE USER ABOUT HIS DAILY AND MONTHLY CONSUMPTION THAT, IN CASE IT HAS A NEGATIVE PRESENTATION ABOUT HIS CONSUMPTION, WILL SHOW A POSITIVE CHANGE IN HIS SPENDING AND HABITS IN THE FUTURE. IN THIS SOFTWARE, IT WOULD BE PUT INTO PRACTICE A SOFTWARE THAT STORES THE DATA THAT THE USER PRESENTS TO THE APPLICATION, FOR EXAMPLE, THE ENTIRE PURCHASE OF THE MONTH WILL BE REGISTERED, PERISHABLE OR NOT, COLD CUTS, CANNED FOOD AND THE LIKE, ALONG WITH ITS EXPIRATION DATE AND ANY INFORMATION THAT THE PRODUCT CARRIES, AS THE DAYS GO BY, THE APPLICATION NOTIFIES WHEN A CERTAIN FOOD IS NEAR ITS EXPIRATION DATE, WHICH ONE SHOULD BE REPLACED IN THE PANTRY AND WHICH ONE WAS LOST, HELPING TO ANALYZE IF IT WOULDN'T BE MORE VIABLE TO REDUCE A CERTAIN CONSUMPTION TO AVOID EXPENSES AND WASTE. THIS PROJECT WILL HELP CONTROL FOOD WASTE, AIMING TO COLLABORATE WITH A MORE ECOLOGICAL AND SUSTAINABLE SOCIETY. WITH THE LAUNCH OF THE APPLICATION WE EXPECT A SIGNIFICANT DECREASE IN FOOD WASTE BY THE CONSUMER, WE STILL CAN'T CREATE A SYSTEM THAT WILL END GLOBAL WASTE, BUT THIS SOFTWARE IS ALREADY A START TO SOLVE A MAJOR PROBLEM THAT AFFECTS US ALL.